2006
DOI: 10.1016/s0377-1237(06)80107-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nebulised Epinephrine versus Salbutamol in Hospitalised Children with Bronchiolitis

Abstract: Nebulised epinephrine is a useful and safe drug for moderate/severe bronchiolitis and is superior to salbutamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…A study by Sanchez et al [6] using clinical scores and pulmonary mechanics in bronchiolitis comparing epinephrine and salbutamol had found epinephrine to be superior. A smaller study using only clinical parameters in cases of bronchiolitis was done by the author which showed a benefit of epinephrine over salbutamol [26]. The current study has demonstrated superiority of epinephrine over salbutamol in both bronchiolitis and WARI.…”
Section: Discussionsupporting
confidence: 48%
“…A study by Sanchez et al [6] using clinical scores and pulmonary mechanics in bronchiolitis comparing epinephrine and salbutamol had found epinephrine to be superior. A smaller study using only clinical parameters in cases of bronchiolitis was done by the author which showed a benefit of epinephrine over salbutamol [26]. The current study has demonstrated superiority of epinephrine over salbutamol in both bronchiolitis and WARI.…”
Section: Discussionsupporting
confidence: 48%
“…5 Nebulized epinephrine is safe for moderate to severe bronchiolitis and is better than salbutamol. 6 Recently a study concluded that using epinephrine instead of salbutamol could be more effective in the management of the disease. This study showed that mean respiratory rate (52.5±4.9 vs. 50±2.9, P<0.05), oxygen saturation (97.1±1.5 vs. 97.9±0.8, P<0.05), mean heart rate (151.8±10 vs 160.2±10.2, P<0.05) and RDAI score (6.4±1.7 vs. 7.7±1.0, p>0.05) were https://doi.org/10.29309/TPMJ/2020.27.12.4726 significantly different in salbutamol and nebulized adrenaline therapy, respectively for management of bronchiolitis in children.…”
Section: Introductionmentioning
confidence: 99%